Cyclopropylmagnesium Scorpionates: A Missing Member of the Series with Both Staggered and Eclipsed Rotamers in the Crystal. Issue 20 (20th April 2018) - Dufrois, Quentin; Mallet‐Ladeira, Sonia; Dinoi, Chiara; Etienne, Michel
Abstract : The reaction of the hydrotris(3, 5‐dimethylpyrazolyl)borate potassium salt KTp Me2 with [Mg( c ‐C3 H5 )2 (dioxane) x ] gives [Tp Me2 Mg( c ‐C3 H5 )] (1 ) in 70 % yield. Full characterization includes an X‐ray diffraction study, which reveals the presence of both staggered and eclipsed rotamers around the Mg–C bond of1 in the unit cell. There is no evidence for any agostic interaction. Complex1 does not undergo the Schlenk equilibrium. The complex [(F12 ‐Tp 4Bo, 3Ph )Mg( c ‐C3 H5 )] (2 ) containing a hydrotris(tetrafluoro‐3‐phenylindazolyl)borate scorpionate ligand, is obtained in 20 % yield. Complex2 proved to be significantly more labile than1, solutions of2 giving readily [Mg(F12 ‐Tp 4Bo, 3Ph )2 ] (3 ). This study emphasizes the importance of tuning the steric and electronic properties of the scorpionate ligands for the stabilization of heteroleptic magnesium alkyl complexes. Abstract : Staggered and eclipsed rotamers of a magnesium cyclopropyl scorpionate are observed in the crystal. Enhancing the electron‐withdrawing properties of the scorpionate ligand leads to ill‐defined chemistry.